The Lymphatic System in Breast Cancer: Anatomical and Molecular Approaches - Gianfranco Natale (MDPI AG, 2021)
Breast cancer is one of the most important causes of premature mortality among women and it is one of the most frequently diagnosed tumours worldwide. For this reason, routine screening for prevention and early diagnosis is important for the quality of life of patients. Breast cancer cells can enter blood and lymphatic capillaries, then metastasizing to the regional lymph nodes in the axilla and to both visceral and non-visceral sites. Rather than at the primary site, they seem to enter the systemic circulation mainly through the sentinel lymph node and the biopsy of this indicator can influence the axillary dissection during the surgical approach to the pathology. Furthermore, secondary lymphoedema is another important issue for women following breast cancer surgical treatment or radiotherapy. Considering these fundamental aspects, the present article aims to describe new methodological approaches to assess the anatomy of the lymphatic network in the axillary region, as well as the molecular and physiological control of lymphatic vessel function, in order to understand how the lymphatic system contributes to breast cancer disease. Due to their clinical implications, the understanding of the molecular mechanisms governing lymph node metastasis in breast cancer are also examined. Beyond the investigation of breast lymphatic networks and lymphatic molecular mechanisms, the discovery of new effective anti-lymphangiogenic drugs for future clinical settings appears essential to support any future development in the treatment of breast cancer.